The Austrian School of Economics and the Mainstream: : a proposal for a dialogue through the DSGE model - Bernardo, Marcel Pereira (2019)
After the 2008, crises in the academic world started to look for differents views that could explain and satisfy the general public about economics phenomena. The Rebulding Macroeconomics Project arises on this context, reuning mainstream economists who made some suggests to improve economics. On the other hand, it’s very important realize that some austrian economists – who predicted the financial crises – were left out or on the sideline of this debate. This paper, therefore, aims to point out the means to be explored by austrian economists for establishing open dialogue and seeking better insertion in the main economic debates, using as reference the project carried out by The Oxford Review nad the DSGE model.